The effect of piezosurgery with cvd tip in osteotomy in rat parietal bone: histologic and histomorphometric analysis - Macedo, Nelson Luiz; Monteiro, Adriana Socorro Ferreira; Sato, Tabata Prado; Macedo, Luís Guilherme Scavone (Brazilian Dental Science, 2015)
Objective: The aim of this study was to compare the response of bone tissue in osteotomy under piezosurgery using a CVD tip in rat parietal bone in contrast with the standard protocol using low-speed tungsten burs. Material and Methods: A bone defect model was created in parietal bone of 20 male Wistar rats using CVD tip and drill. Five animals were sacrificed after 3, 7, 14 and 28 days and the bone containing the defects was submitted to the histologic and histomorphometric analysis. The results of histomorphometry were statistically analyzed using RM ANOVA with a significance level of ? = 0.05. The results were still subjected to Tukey's multiple comparison test. Results: The results showed statistically significant difference (p